Prevalence and association with birth outcomes of low vitamin D levels among pregnant women living with HIV. (15th July 2021) - Bergløv, Anne; Moseholm, Ellen; Katzenstein, Terese L.; Johansen, Isik S.; Storgaard, Merete; Pedersen, Gitte; Weis, Nina
Abstract : Objectives: To evaluate the prevalence of low vitamin D levels among well treated pregnant women living with HIV (WLWH) on combination antiretroviral therapy in Denmark, to identify risk factors of low vitamin D levels, and to assess the association between vitamin D status and birth outcomes. Design: Nationwide cohort study. Methods: All WLWH in Denmark giving birth from 2000 to 2018 with a vitamin D measurement during pregnancy were identified. Risk factors for low vitamin D (deficiency or insufficiency) were assessed using log-binomial regression models, both univariate and adjusted for maternal and HIV factors. The association between vitamin D status and birth outcomes was assessed using linear regression models for continuous outcomes and log-binomial models for binary outcomes. Results: Among 208 WLWH, the prevalence of vitamin D deficiency was 13%, insufficiency 34%, and sufficiency 53%. Being of African origin (RR 2.68, P = 0.01), Asian origin (RR 3.38, P = < 0.01), or having HIV RNA levels more than 50 copies/ml (RR 1.43, P = 0.04) was associated with an increased risk of low vitamin D level. WLWH with vitamin D deficiency had an increased risk of preterm birth (RR 2.66, P = 0.03) and giving birth to small for gestational age (SGA) children (RR 6.83, P = 0.02) compared with WLWH with sufficient vitamin D level. Conclusion: Low vitamin D level was prevalent among well treated pregnant WLWH in Denmark, especially among women of African or Asian origin, and women with detectable viral loads. Vitamin D deficiency was associated with an increased risk of preterm birth and SGA. Abstract : Supplemental Digital Content is available in the text